Social identity and expectations for employment of students with disabilities - Gostenina Valentina; Melnikov Sergey; Lapyko Tatyana (E3S Web of Conferences, 2023)
Various technologies of influencing social processes and attitudes of people in order to provide assistance to the population and certain categories of citizens in difficult life situations make researchers turn to basic social categories and demonstrate their role in applied spheres of human life organization. The article shows the sociological category of social identification as a technology for implementing social expectations of students with disabilities. Based on the results of sociological research (questionnaire survey) practical recommendations are developed to inform students with disabilities about the social and educational space of the university for employment.